Analysis of the Use Intelligent Guess and Test Strategy in Solving Realistic HOTS Problems for Junior High School Students - Wibawa, Kadek Adi; Wena, I Made; Arsana, Anak Agung Putu; Saelee, Sompob (Proceeding International Conference on Mathematics and Learning Research, 2024)
There are various strategies for solving realistic HOTS-type problems, one of which is the intelligent guess and test strategy. However, students have not yet fully understood the use of this strategy. Therefore, this study aims to analyze the use of the intelligent guess and test strategy in solving realistic HOTS-type problems. This research employs a qualitative approach with a case study type. The study was conducted at SMP Widiatmika in Badung Regency, Bali Province, involving 27 eighth-grade students. Data collection techniques included tests and documentation. Data analysis employed qualitative content analysis, thematic coding, constant comparative analysis, and narrative analysis. The results of this study indicate that 96.3% of students chose to solve problems using an arithmetic approach, while 3.7% used an algebraic approach. The study also revealed that students faced difficulties in solving realistic HOTS-type problems, particularly in understanding the problems and determining the methods to use. Furthermore, the study identified three patterns in the use of the intelligent guess and test strategy: incomplete, complete but indirect, and complete and direct. The incomplete pattern occurs when students determine a formula without a strong basis to arrive at the final answer to a problem. The second pattern, complete but indirect, begins after the student understands the problem and makes the most reasonable guess, followed by testing. The student then analyzes the test results and makes the next guess based on the initial guess. This process is carried out cyclically until the student finds the most accurate guess. The third pattern, complete and direct, occurs when the student makes a direct guess because they fully understand the problem and have considered various aspects of the issue. The student tests the first guess and obtains the expected result.